New Islamic equity style indices: Constructing and testing the efficacy of information transmission - Shahrin Saaid Shaharuddin; Wee-Yeap Lau; Rubi Ahmad (Cogent Economics & Finance, 2017)
The non-existence of commercially available Islamic Equity Style Indices from index providers such as MSCI especially on small value and small growth stocks motivates us to construct our new indices. Firstly, various index construction methods are compared. Secondly, this paper describes in detail the process of index construction and finally, the new indices are tested using out-of-sample forecast and trading strategies. Notably, our results show Large Growth (LG) and Large Value (LV) indices have more efficacy compared to Small Growth (SG) and Small Value (SV) stocks. From the perspective of Islamic financial market, the creation of Islamic equity style index enables new strategies which focus on size, value, and smart beta. In addition, the out-of-sample VAR forecast indicates that LG and LV indices are the best candidates for creating a new benchmark for portfolio diversification. Furthermore, by applying simple trading strategies and selecting Islamic value and small market capitalization stocks, our evidence shows that Islamic equity style indices have benefits for investors and fund managers. To the best of authors' knowledge, this paper is the first attempt to create non-commercially available Islamic equity style indices.
Keywords: 330; Islamic capital markets; stock market index; equity style index; information transmission; vector autoregression